2021
DOI: 10.12793/tcp.2021.29.e14
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of important pharmacogenes in Koreans using the DMET™ platform

Abstract: Genetic polymorphisms of enzymes and transporters associated with the absorption, distribution, metabolism, and elimination (ADME) of drugs are one of the major factors that contribute to interindividual variations in drug response. In the present study, we aimed to elucidate the pharmacogenetic profiles of the Korean population using the Affymetrix Drug Metabolizing Enzyme and Transporters (DMET™) platform. A total of 1,012 whole blood samples collected from Korean subjects were genotyped using the DMET™ plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In the present study, we observed to following allele frequencies: 63.0% for CYP2C19*1, 26.4% for CYP2C19*2, 9.4% for CYP2C19*3, and 1.3% for CYP2C19*17. The frequency of the CYP2C19*17 allele was similar to that reported by other Korean (0.3%-1.5%) or Asian (0.5%-3%) studies, and was lower than that reported for Caucasians (15.4%-33.8%) or Africans (10%-18%) (Sim et al 2006;Kim et al 2010;Li-Wan-Po et al 2010;Ramsjö et al 2010;Scott et al 2011;Kim et al 2021). Based on the ability to metabolize CYP2C19 substrates, individuals are categorized into the five phenotype categories recommended by the Clinical Pharmacogenetics Implementation Consortium (CPIC), as follows: PMs, IMs, NMs; formerly known as extensive metabolizers (EM), RMs, and ultrarapid metabolizers (Caudle et al 2017;Lee et al 2022).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, we observed to following allele frequencies: 63.0% for CYP2C19*1, 26.4% for CYP2C19*2, 9.4% for CYP2C19*3, and 1.3% for CYP2C19*17. The frequency of the CYP2C19*17 allele was similar to that reported by other Korean (0.3%-1.5%) or Asian (0.5%-3%) studies, and was lower than that reported for Caucasians (15.4%-33.8%) or Africans (10%-18%) (Sim et al 2006;Kim et al 2010;Li-Wan-Po et al 2010;Ramsjö et al 2010;Scott et al 2011;Kim et al 2021). Based on the ability to metabolize CYP2C19 substrates, individuals are categorized into the five phenotype categories recommended by the Clinical Pharmacogenetics Implementation Consortium (CPIC), as follows: PMs, IMs, NMs; formerly known as extensive metabolizers (EM), RMs, and ultrarapid metabolizers (Caudle et al 2017;Lee et al 2022).…”
Section: Discussionsupporting
confidence: 87%
“…Although reports of the frequency of the CYP2C19*10 allele are scarce, it exhibited a low frequency of less than 1% (Table 3) (Nakamoto et al 2007;Rasmussen and Werge 2008;Langaee et al 2014;Khalil et al 2016;Kim et al 2021;Goljan et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the indirect cost of acute myocardial infarction in Korea accounted for 42.3% of the total costs in 2012 31 . Therefore, the calculated benefit in our study would be the minimal estimate but could suggest implementing cost‐effective genotype panels 32 …”
Section: Discussionmentioning
confidence: 87%
“…31 Therefore, the calculated benefit in our study would be the minimal estimate but could suggest implementing cost-effective genotype panels. 32 The cost-effectiveness of pre-emptive genotyping compared to reactive genotyping is still on debate. Reactive genotyping is easier to perform and has already shown cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation